Project Managers’ Perceptions on Barriers to Effective Stakeholder Management (ESM) in Multifarious Infrastructure Projects (MIPs) Delivery in Nigeria - Zarewa, G. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Many projects were known to have failed due to ineffective stakeholder management. This study investigated views of Project Managers (who participated in the delivery of Multifarious Infrastructure Projects (MIPs) in north eastern and north western regions of Nigeria) on barriers to Effective Stakeholder Management (ESM) in MIPs delivery in Nigeria. The study was conducted with the aim of preventing or at least minimising the projects’ failure rates due to ineffective stakeholder management. Extensive literature review, questionnaire survey, and Relative Importance Index (RII) analysis methods were used to conduct the study. Barriers to ESM in the projects’ delivery were identified and ranked according to the project managers’ perceptions on their respective levels of influence against ESM. The study discovered that barriers with different levels of impact inhibit effective stakeholder management in MIPs delivery. Client’s Uncooperative Attitude; Failure to Identify Potential Conflict Areas; Uncooperative Attitude of Stakeholders; Project Manager’s Poor Knowledge of Stakeholder Management/Failure to Understand Stakeholders’ Needs and Expectations; and Failure to Meet Information Requirements of all Stakeholders were ranked as the first, second, third, fourth and fifth (in descending order) barriers to ESM in MIPs delivery respectively. The study concluded that current approach to stakeholder management in MIPs needs to be improved considerably and accordingly recommends the development of an appropriate strategy for handling stakeholder management in the delivery of MIPs and other projects in Nigeria.